Penerapan Mesin CNC Router Milling dan Pendampingan Batik Mark untuk Meningkatkan Proses Produksi pada UMKM Batik Ndilkoro di Rejosari Malang - Dani Irawan; Erwin Komara Mindarta; Didin Zakariya Lubis (CV. IRA PUBLISHING, 2023)
UMKM Batik Ndil Koro, it is obtained that the process of making batik is less effective and efficient. At the time of the production process and the level of production speed, it was still done manually by the Cap Ndil Koro batik craftsmen. Based on this background, the community service team through internal UM funds intends to hold community service (1) Produce appropriate technology in the form of a CNC Router Milling Machine to improve the production process at UMK batik Ndilkoro for service partners, (2) Conduct technical guidance on the use of CNC tools Router Milling so that the production of batik can be increased in terms of quality and quantity, and the integration component of batik design and manufacture has been designed and prototyped. This component consists of a design system using the motif recognition method, and a computer-based CNC batik machine. The prototype has been successfully tested. System testing is done by designing batik motifs that are quite complex then transferring them into G-Code data and finally reading it to control the machine. The level of precision that is measured by testing simple images in the form of lines and rectangles can reach a precision level of up to 0.17mm, and this system is capable of producing the results. has a decent level of economic feasibility for investment. However, caution is needed in its application to avoid culture shock because it involves changes in production methods that are very different, so it is advisable to carry out socialization, education and transition programs by stakeholders, especially local governments.